Mycobacterium tuberculosis Promotes Apoptosis in Human Neutrophils by Activating Caspase-3 and Altering Expression of Bax/Bcl-xL Via an Oxygen-Dependent Pathway - Nasrin Perskvist; Min Long; Olle Stendahl; Limin Zheng (2002)
Abstract In addition to direct bactericidal activities, such as phagocytosis and generation of reactive oxygen species (ROS), neutrophils can regulate the inflammatory response by undergoing apoptosis. We found that infection of human neutrophils with Mycobacterium tuberculosis (Mtb) induced rapid cell death displaying the characteristic features of apoptosis such as morphologic changes, phosphatidylserine exposure, and DNA fragmentation. Both a virulent (H37Rv) and an attenuated (H37Ra) strain of Mtb were equally effective in inducing apoptosis. Pretreatment of neutrophils with antioxidants or an inhibitor of NADPH oxidase markedly blocked Mtb-induced apoptosis but did not affect spontaneous apoptosis. Activation of caspase-3 was evident in neutrophils undergoing spontaneous apoptosis, but it was markedly augmented and accelerated during Mtb-induced apoptosis. The Mtb-induced apoptosis was associated with a speedy and transient increase in expression of Bax protein, a proapoptotic member of the Bcl-2 family, and a more prominent reduction in expression of the antiapoptotic protein Bcl-xL. Pretreatment with an inhibitor of NADPH oxidase distinctly suppressed the Mtb-stimulated activation of caspase-3 and alteration of Bax/Bcl-xL expression in neutrophils. These results indicate that infection with Mtb causes ROS-dependent alteration of Bax/Bcl-xL expression and activation of caspase-3, and thereby induces apoptosis in human neutrophils. Moreover, we found that phagocytosis of Mtb-induced apoptotic neutrophils markedly increased the production of proinflammatory cytokine TNF-α by human macrophages. Therefore, the ROS-dependent apoptosis in Mtb-stimulated neutrophils may represent an important host defense mechanism aimed at selective removal of infected cells at the inflamed site, which in turn aids the functional activities of local macrophages.